Flecainide and risk of skin neoplasms: Results of a large nested case–control study in Spain and Denmark - Reyes, Carlen; León-Muñoz, Luz M; Pistillo, Andrea; Jóhannesdóttir Schmidt, Sigrún Alba; Kristensen, Kasper Bruun; Puente, Diana; LLorente-García, Ana; Huerta-Álvarez, Consuelo; Pottegård, Anton; Duarte-Salles, Talita (Frontiers in Pharmacology, 2022)
Background: A previous study in Denmark suggested an increased melanoma risk associated with the use of flecainide. Objective: To study the association between flecainide use and the risk of melanoma and non-melanoma skin cancer in Spain and Denmark. Methods: We conducted a multi-database case–control study in (database/study period) Spain (SIDIAP/2005–2017 and BIFAP/2007–2017) and Denmark (Danish registries/2001–2018). We included incident cases of melanoma or non-melanoma skin cancer (NMSC) aged ≥18 with ≥2 years of previous data (≥10 years for Denmark) before the skin cancer and matched them to controls (10:1 by age and sex). We excluded persons with immunosuppression or previous cancer. We defined ever-use as any prescription fill and high-use as a cumulative dose of at least 200 g (reference: never-use). We categorized a cumulative dose for a dose–response assessment. We used conditional logistic regression to compute ORs (95% CI) adjusted for photosensitizing, anti-neoplastic, disease-specific drugs and comorbidities. Results: The total numbers of melanoma/NMSC cases included were 7,809/64,230 in SIDIAP, 4,661/31,063 in BIFAP, and 27,978/152,821 in Denmark. In Denmark, high-use of flecainide was associated with increased adjusted ORs of skin cancer compared with never-use [melanoma: OR 1.97 (1.38–2.81); NMSC: OR 1.34 (1.15–1.56)]. In Spain, an association between high-use of flecainide and NMSC was also observed [BIFAP: OR 1.42 (1.04–1.93); SIDIAP: OR 1.19 (0.95–1.48)]. There was a non-significant dose–response pattern for melanoma in Denmark and no apparent dose–response pattern for NMSC in any of the three databases. We found similar results for ever-use of flecainide. Conclusion: Flecainide use was associated with an increased risk of melanoma (Denmark only) and NMSC (Denmark and Spain) but without substantial evidence of dose–response patterns. Further studies are needed to assess for possible unmeasured confounders.